Seroprevalence of Toxoplasma gondii in Goats in Two Districts in Northern Palestine - Rateb Aref OTHMAN (Walailak Journal of Science and Technology, 2013)
The objective of this study was to investigate the presence of anti-T. gondii in goats raised on farms in the Jenin and Tulkarm districts in the north of Palestine. The investigation was conducted on 14 herds comprising of 280 goats. Blood samples were collected via the jugular veins of 151 goats during the period from January to December 2011. The indirect ELISA test was used for the detection of anti-T. gondii antibodies. Results showed that an anti-T.gondii IgG antibody was detected in 13.4 % of the samples. The presence of the anti-T. gondii antibody was influenced by the location of the goat herds. The highest incidence was in Jenin district (17.44 %) while it was 7.69 % in Tulkarm district. These results indicated the possible contamination of meat and milk of the goats with this parasite, which in turn negatively affects human health.